High Efficiency (22.46) of Solar Cells Based on Perovskites - raheem, zainab; Zainab. R. Abdulsada,; Sally Basim Kadhim,; Samir M . AbdulAlmohsin,; Hayder Saadoon Abdulaali, (University of Thi-Qar Journal of Science, 2023)
In this research we have considered (CH₃NH₃PbX₃) (X=I,Cl,Br) as an absorber layer and Cu2O/spiro-OMeTAD/ P3hT/PEDOT:PSS as (HTM) along with PCBM/TiO₂ as (ETM). It is a solid-state planar heterojunction p-i-n solar cell with low p-type-doped, CH₃NH₃PbX₃ sandwiched between the p-type is called HTM layer and n-type. SCAPS-1D simulation software is used for numerical simulation to examine the influence of various electrical factors on the efficiency PCBM/CH₃NH₃PbCl3/P3hT,PCBM /CH₃NH₃PbI₃/P3hT,PCBM/MAPbCl₃/Cu2O,TiO2/MAPbCl₃/Sipro-OMeTAD, TiO₂/MAPbI3/Sipro-OMeTAD, PCBM /CH₃NH₃PbBr3/ PEDOT:PSS, and PCBM /CH₃NH₃PbI₃/ PEDOT:PSS heterojunction-based perovskite solar cell structures. With these variables an efficiency of 22.46% was obtained at 263.15(k). By using SCAPS simulation software